Use of Communication Media for Assisting the Family Hope Program (PKH) in Family Development Sessions (FDS) to Improve the Quality of Beneficiary Families in Samasundu, Polewali Mandar Regency - Kaharuddin, Kaharuddin (Al-Iftah: Journal of Islamic studies and society, 2021)
This thesis discusses the Use of Complementary Communication Media for the Family Hope Program in the Family Development Session to Improve the Quality of Beneficiary Families in Samasundu Village, Polewali Mandar Regency. The purpose of this thesis research is to obtain empirical data on the communication media used by the Family Hope Program Facilitator in Improving the Quality of Beneficiary Families in the Family Development Session in Samasundu Village, Polewali MandarRegency. This type of research is empirical research. The research paradigm is naturalism. Primary data sources are companions of community leaders, village government and community beneficiaries of the Family Hope Program, Samasundu Village, Polewali Mandar Regency, while secondary data are scientific books, journals and theses. The research instrument was the researcher himself and was assisted by data collection methods, namely observation guidelines, interview guidelines, documentation tools and field notes. Data collection techniques are observation, interviews, and documentation. Data processing and analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The data validity testing technique uses triangulation technique. The results of this study are: (1) The use of communication media in the FDS material in the form of videos and flipcarts and in the FDS material makes it easier for beneficiary mothers to receive material from the companion. (2) The quality of the families receiving the Program Keluarga Harapan Benefits in the health, education and economy pieces of this high quality is because the assistance provided by the central government through the Ministry of Problems is used appropriately so as to result in a healthy family and towards a prosperous family. (3) With the existence of the Family Development Session material, it is able to help the beneficiaries of the Keluarga Harapan Program to be advanced and independent and have broad knowledge and abilities so that they can take an effective role in building an independent prosperous family .